Recent trends in soft beverages - Rao, L. Jagan Mohan; Ramalakshmi, K. (Woodhead Pub. India, 2011)
This book discusses recent trends in soft beverages. Chapters discuss chemical composition, health benefits and by-products. Recent trends in value addition are also examined in detail.
Keywords: Beverages.; Coffee.; Tea.; Soft drinks.; elektronické knihy; electronic books